Priority Topics for Panel Engagement in Health Guideline Development - Wiercioch, Wojtek (My University, 2020)
Health care guidelines provide a means of assessing the best available research evidence on a given health care topic and offering recommendations about use of specific interventions and management of patient care. Guidelines allow clinicians, patients, health administrators and policy-makers to be efficiently informed and stay up to date on alternative care options. The development of guidelines is a complex and multidisciplinary process, with a defining feature of involving a panel of experts in steps such as selecting health care questions, assessing the research evidence, making judgements about health benefits and harms, and, ultimately, formulating recommendations. Guideline methodology has advanced over the past decades, including establishment of specific steps and standards to ensure trustworthiness of guidelines. However, there remain critical research questions on how to best accomplish and reach these standards, including how to best engage panels in the steps. This thesis presents a body of research on the development and evaluation of new methods for decision-making and considering health outcomes in guidelines, prioritizing health care questions for guidelines, and evaluating the guideline development process. It includes three studies: 1) a methodological study on developing health outcome descriptors to define health outcomes considered in decision-making by guideline panels; 2) a methodological study and randomized controlled trial to evaluate specific criteria for panels to consider when prioritizing health care questions for guidelines and to judge the importance of health outcomes; and 3) an instrument development and validation study to create a tool for panel members to evaluate the appropriateness of the guideline development process they participate in. In these studies, we established a method and steps for creating health outcome descriptors with panels, aimed at achieving consistency in how health outcomes are considered throughout the guideline development process, from prioritization to formulating a recommendation on the basis of those outcomes. The structured approach and criteria evaluated for prioritization of healthcare questions informed panel deliberations and decisions about choosing questions for their guideline topics, and the proposed methods for outcome prioritization facilitated panels in informing what the critical and important outcomes were for decision-making. Finally, the instrument we developed facilitated members of guideline panels to provide their assessment of the guideline development process and identify strengths and weaknesses and areas for improvement. Our findings will allow organizations responsible for guideline development to apply the new methods with their panels and to evaluate their guideline processes to inform quality-improvement efforts.
Keywords: clinical practice guidelines; expert panels; health recommendations; clinical decision-making